Improving Network Security: Protection Strategies in the Digital Age - Andre, Muhammad Fabio; Alfarizi, Ferdian; Falssava, Jossa Neka; Sulistiani, Heni (IC-ITECHS, 2024)
Network security is an important factor in protecting data in the digital era. Threats such as DDoS attacks and malware can damage information systems. This article discusses network protection strategies, including the use of firewalls, encryption, VPNs, and Zero Trust Security. In addition, the implementation of multi-factor authentication and user awareness are also identified as crucial mitigation measures. By utilizing technologies such as artificial intelligence, threat detection can be done more efficiently. This research aims to provide practical solutions to improve network security and reduce the risk of cyber attacks.